Spatial Reasoning: A Survey on the 8th Grader Students' Gain in Online Learning - Fitriyani, Harina; Kusumah, Yaya Sukjaya; Turmudi, Turmudi (Universitas Ahmad Dahlan, 2021)
Coronaviruses disease (Covid-19) pandemic forces schools to implement schools from home through online learning. This study aims to describe online mathematics learning, examine differences in aspects of spatial reasoning, and spatial reasoning based on gender. We conducted a survey method on 140 participants in one private junior high school in Yogyakarta. Data collection using an spatial reasoning test via Google Form consist of nine questions and direct interview with a teacher through video conference. Data analysis uses descriptive and inferential statistics. The results showed that online mathematics learning using the Google Form platform can assist students with limited facilities in learning process. The research finding showed no difference in spatial reasoning ability between male and female students, including in each aspect of spatial reasoning. In addition, other findings indicate that the aspect of spatial reasoning that students master the most is spatial visualization, while the aspect of spatial reasoning that is the least mastered by students is spatial relations.